CAREGIVER'S STRESS OF PSYCHIATRIC PATIENTS - Darlami, Kamala; Ponnose, Reshmi; Jose, Pradap (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Psychiatric disorders are as old as human life. The prevalence of psychiatric disorders and their undesired personal, familial and social effects have increased simultaneously with population growth and urbanity. Limited psychiatric health care services coupled with increased psychiatric disorders led their families to play a critical role in taking care of the patients and they have to be considered as a main source of patients' caregivers. Long term care to psychiatric patients' increases caregivers' burden and decreases their mental health status. This may result in increasing psychiatric stress of caregivers and decreased patient care. MATERIAL AND METHODS: A descriptive research design was adopted to assess the caregiver's stress of psychiatric patients and coping mechanisms in this study. Fifty care givers of the psychiatric patients were selected through purposive sampling technique from inpatient and outpatient units of Universal College of Medical Sciences, Teaching Hospital. Modified and combined version of General Health Questionnaire-12 and Kingston caregiver scale, Cope scale and demographic performa were used to interview the samples. Collected data was analysed using descriptive and inferential statistics. Sociodemographic data was analyzed using frequency and percentage. Level of stress and coping was analyzed by computing frequency, percentage, mean, median, and standard deviation. The association between the caregiver's stress with sociodemographic variables was computed using chi-square test. RESULT: Result related to stress level of respondents revealed that majority of the respondents (86%) were at moderate stress, followed by 14% with severe stress. Study findings showed that caregivers were stressed with care giving, family and financial issues. In relation to coping strategies, 68% of respondent used active coping measures whereas 32% adopted passive coping methods. Majority of the respondents used social support, positive reinterpretation and religious coping strategies to overcome the stress. Caregiver's stress compared with sociodemographic variables showed a significant association between religion, ethnicity, education, marital status, onset of illness, type of illness, type of patient and relation with patient. CONCLUSION: The present study revealed that all of the respondents were under stress and most of them used active coping measures to manage their stress. The study has important implications for service delivery and clinical practice. Health care personnel should be observant of psychological problems of caregivers and if subjective complaints or functional impairment are present, evaluation and therapeutic interventions should be suggested. Information regarding support and practical assistance should also be offered to families of psychiatric patients. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 39-43